ANALYSIS OF VERBS EQUIVALENCE IN ENGLISH-INDONESIAN TRANSLATION OF THE SHORT STORY THE BOGEY-BEAST - Hisasmaria Hisasmaria (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
This research is about the analysis of verbs equivalence in translating the short story The Bogey-Beast. The research was conducted by using qualitative method. The source of the data was collected from the short story the Bogey-Beast and its translation in Indonesian and the data was restricted on the verbs. The objective of the research is to find out the type of verbs equivalence in the short story the Bogey-Beast and its translation, the most dominan type of equivalence found in the short story text, and the naturalness of expression in the translation of short story the Bogey-Beast. The data was analyzed based on Nida (McGuire, 1991) theory about translation equivalence. There are two types of equivalences, they are: (1) Formal Equivalence, which focus attention on the message itself, in both form and content, and (2) Dinamic Equivalence translation, which is based upon the principle of equivalence effect.